MUP451 : Performance forum II / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2024)
This course provides an avenue primarily for students to observe peer performances and classify performance standards, develop concert etiquette, critique musical presentations and participate in talks by invited guest speakers and performers. Music Performance majors are required to demonstrate through performance, the ability to distinguish stylistic practices of at least two pieces on their principal instrument. Students attend concerts and write concert reviews.